Evaluation of Serum Uric Acid as a Potential Predictive Biomarker in Pulmonary Arterial Hypertension - Monalisa Mohapatro; Satya Narayan Routray; Biswakesh Panigrahy; Pratima Kumari Sahu; Suryasnata Jena (Jurnal Kardiologi Indonesia, 2026)
Background: Pulmonary arterial hypertension (PAH) is a relatively rare fatal disease, confounding many cardiopulmonary diseases. Systolic pulmonary artery pressure (sPAP), measured by transthoracic echocardiography, can be taken as a surrogate marker for diagnosing this disease. Uric acid, a marker of oxidative stress, has been investigated as a potential predictive biomarker for risk stratification. Our study was conducted to ascertain the incidence and severity of sPAP, to evaluate the level of uric acid levels, and to establish a correlation. Methods: This is an observational case-control study that included 51 cases of PAH diagnosed by sPAP ≥36 mm Hg, along with 51 controls. Serum uric acid was assayed using a spectrophotometric method. Statistical analysis was performed using Microsoft Excel and SPSS version 20.0. Results: Cases were observed in the range of 24 to 87 years (average 48 years) with female predominance. Uric acid levels were significantly higher in cases than in controls. Females showed slightly lower levels of uric acid as compared to males. Correlation analysis indicated a significant positive correlation between sPAP and uric acid levels. Receiver operating characteristic (ROC) analysis demonstrated that serum uric acid had 68% predictive accuracy for sPAP severity at a cutoff of 5.45 mg/dL. Conclusion: The level of uric acid, a routine biomarker analysed in laboratories, is found to be increased in PAH patients and closely correlates with the severity of sPAP. This suggests a potential role of uric acid as a predictive biomarker in PAH management.